Comparison of metagenomic next-generation sequencing and blood culture for diagnosis of bloodstream infections - Yu, Juan; Zhang, Li; Gao, Deyu; Wang, Jie; Li, Yi; Sun, Ning (Frontiers in Cellular and Infection Microbiology, 2024)
Objectives: This study aimed to evaluate the clinical performance of plasma cell-free DNA (cfDNA) next-generation sequencing (NGS) in for pathogen detectionthe detection of pathogens in septic patients with sepsis.Methods: A total of 43 pairs of blood and plasma samples form 33 blood culture-positive patients were used as testing samples in metagenomic next-generation sequencingNGS (mNGS) and NGS of 16S ribosomal RNA gene amplicons (16S rRNA NGS). The results of routine tests, including microbial culture, complete blood count, and biochemical tests, were collected from the electronic medical records.Results: Using blood as an mNGS testing samples, the proportion of host DNA is was 99.9%, with only 3 three bacteria detected and no fungi detected. When using plasma in mNGS, the proportion of host DNA is was approximately 97%, with 84 bacteria and 2 two fungi detected. Notably, 16S rRNA NGS detected 15 and 16 bacteria in 43 pairs of blood and plasma samples, respectively. Blood culture detected 49 bacteria (23 Ggram-negative bacilli and 26 gGram-positive cocci) and 4 four fungi, with 14 bacteria considered contaminants by clinical microbiologists. For all blood cultures, plasma cfDNA mNGS detected 78.26% (19/23) gramgram-negative rods, 17% (2/12) gramgrampositive cocci, and no fungi. Compared to blood cultures, the sensitivity and specificity of plasma cell-free cfDNA mNGS for detecting bacteria and fungi were 62.07% and 57.14%, respectively.Compared to blood, plasma is more suitable for the detection of bloodstream infections by using mNGS and is less affected by host DNA. The positive detection rate of plasma cfDNA mNGS for bloodstream infections caused by gGram-negative bacteria is was higher than that caused by gGram-positive cocci.